P259 Tiotropium Handihaler® And Respimat® In Copd: A Safety Analysis On Pooled Data. (10th November 2014) - Halpin, DMG; Dahl, R; Hallmann, C; Leimer, I; Mueller, A; Tashkin, DP
Abstract : Rationale: Tiotropium has been approved and marketed via HandiHaler® (18 µg once daily [qd]) since 2002 and via Respimat® (5 µg qd) since 2007. The recent TIOSPIR™ (TIOtropium Safety and Performance In Respimat®) study demonstrated that both products had comparable safety profiles; the objective of this analysis was to provide an updated safety evaluation of tiotropium in both formulations. Methods: Analysis of pooled adverse events (AEs) from randomised, double-blind, parallel-group, placebo-controlled clinical trials of ≥4 weeks' duration where either tiotropium HandiHaler® 18 µg or tiotropium Respimat® 5 µg was indicated for chronic obstructive pulmonary disease (COPD). Rate ratios (RRs), incidence rates (IRs) and 95% confidence intervals (CIs) were determined for HandiHaler® and Respimat® trials together and separately. Results: This analysis of 28 HandiHaler® and seven Respimat® studies provided 14, 909 (12, 469 and 2440 with HandiHaler® and Respimat®, respectively) patient-years' exposure to tiotropium. Mean age was 65 years and mean forced expiratory volume in 1 second was 1.16 L (41% predicted). The risk (RR [95% CI]) of AEs (0.90 [0.87, 0.93]) and serious AEs (0.94 [0.89, 0.99]) was significantly lower with a numerically lower risk of death (0.90 [0.79, 1.01]) in the tiotropium group (pooled results) (Table ). When separated by device, the risk of AEs and serious AEs remained lower in the tiotropium groups than placebo: RR 0.88 and 0.94 for HandiHaler® and 0.94 and 0.94 for Respimat® for AEs and serious AEs, respectively. Risks for cardiac events (0.93 [0.85, 1.02]) and major adverse cardiovascular events (MACE) (0.87 [0.75, 1.01]) were numerically lower and risk for respiratory, thoracic and mediastinal disorders (0.76 [0.61, 0.96]) was significantly reduced in the tiotropium group. The typical anticholinergic effects of dry mouth (2.39 [2.01, 2.84]), constipation (1.28 [1.06, 1.54]), intestinal obstruction (3.80 [1.42, 10.12]), dysuria (2.16 [1.31, 3.57]) and urinary retention (1.93 [1.21, 3.09]) were higher in the tiotropium group. Conclusions: The results from this safety review do not indicate an increased overall risk for fatal or cardiovascular events during tiotropium treatment, given via HandiHaler® or Respimat®, in patients with COPD.